2019
DOI: 10.1038/s41598-019-51648-1
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin and Dulaglutide are Effective against Obesity-induced Airway Hyperresponsiveness and Fibrosis in A Murine Model

Abstract: Patients with asthma with obesity experience severe symptoms, are unresponsive to conventional asthma treatment, and lack proper pharmacotherapy. Empagliflozin and dulaglutide, developed for diabetes, reduce weight, decrease insulin resistance, and exert additive effects. We evaluated the efficacy of empagliflozin, dulaglutide, and their combination on obesity-induced airway hyperresponsiveness (AHR) and lung fibrosis using a murine model. We assigned C57BL/6J mice to five groups: control, high-fat diet (HFD),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Although better glucose control from GLP1RAs may lead to low incidence of pneumonia in T2D that cannot completely explain the benefits from GLP1RAs on all the nine kinds of respiratory conditions assessed in the study. In contrast, some possible mechanisms for the benefits from GLP1RAs on relevant respiratory diseases are revealed by several small sample human studies 12,13 and animal studies 14,15 in which GLP1RAs were observed to benefit for COPD, 12,13 airway hyperresponsiveness, 14 and acute lung injury 15 via immunomodulating and antiinflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although better glucose control from GLP1RAs may lead to low incidence of pneumonia in T2D that cannot completely explain the benefits from GLP1RAs on all the nine kinds of respiratory conditions assessed in the study. In contrast, some possible mechanisms for the benefits from GLP1RAs on relevant respiratory diseases are revealed by several small sample human studies 12,13 and animal studies 14,15 in which GLP1RAs were observed to benefit for COPD, 12,13 airway hyperresponsiveness, 14 and acute lung injury 15 via immunomodulating and antiinflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…The lung tissue samples were sectioned (2–3 μ m) and stained with hematoxylin and eosin (H&E) and periodic acid-Schiff (PAS) using standard histological protocols to detect mucus-containing cells [ 41 ]. Goblet cell hyperplasia was measured, and fibrosis was assessed, as previously described, using Masson's trichrome stain [ 42 ]. Tissue sections were examined using an Olympus BX53 microscope with an Olympus DP71 digital camera (magnification, 400x; Olympus DP71, Nishi Shinjuku 2-Chome, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Magnetic resonance elastography (MRE) has been used for assessing the stage and severity of liver fibrosis in diabetic patients via measuring liver stiffness [329,330]. [331]. Even though MRE and VCTE can assess liver stiffness, they only provide indications regarding the extent of liver fibrosis, corroborating the notion that only one type of imaging technique is insufficient to fully elucidate the fibrotic signature.…”
Section: Imaging Fibrosis In Diabetesmentioning
confidence: 99%